Who gets visited in prison?: individual- and community-level disparities in inmate visitation experiences - Cochran, Joshua C. (Crime & delinquency, 2017)
Scholarship has shown that visitation helps individuals maintain social ties during imprisonment, which, in turn, can improve inmate behavior and reduce recidivism. Not being visited can result in collateral consequences and inequality in punishment. Few studies, however, have explored the factors associated with visitation. This study uses data on Florida inmates to identify individual- and community-level factors that may affect visitation. Consistent with expectations derived from prior theory and research, the study finds that inmates who are older, Black, and who have been incarcerated more frequently experience less visitation. In addition, inmates who come from areas with higher incarceration rates and higher levels of social altruism experience more visits. Unexpectedly, however, sentence length and economic disadvantage are not associated with visitation. Implications of these findings are discussed.